Leviathan calling: some notes on sociological anti-statism and its consequences - du Gay, Paul (Journal of sociology (Melbourne, Vic.), 2012)
A spectre has haunted many forms of ‘social’ explanation over the course of the last century – the spectre of anti-statism. For not a few sociologists and social theorists, the state has long been regarded as the medium of enslavement, the very antithesis of what they take to be ‘civil society’. Here the state is viewed as a cold monster whose conducts (impersonalism, coercion, indifference, authority – the list is potentially endless) need to be relentlessly exposed and critiqued for their malign influence on the ‘whole human being’ and on ‘society’, which is seen as a naturally occurring phenomenon. This article argues that this enduring opposition between state and civil society represents an unfortunate error, arising from a perverse tradition which would do away with the state. This problematic tradition was born in liberal and democratic ideas of civil society, was embodied in the romantic apotheosis of the purely and metapolitically social, was radicalized by Marxist designs for a society without a state, and culminated in Nazism and Communism. It has survived, however, frequently ‘in mufti’, into our own times and can be found in the social sciences, inter alia, in contemporary social constructionist analyses, such as those associated with certain Foucauldian analytics of ‘government’, and in the moralizing edicts of ‘cosmopolitanism’. Against this tradition, the article sees the state as a remarkable, if fragile, achievement, whose withering away does and will continue to bring forth (predictable) monsters. Rather than the antithesis of society, the state is the major vehicle of human liberty, of social peace and security, and, paradoxically, provides sanctuary for the political critics who attack it.